21st Century Surface Science a Handbook - Pham, Phuong; Goel, Pratibha; Kumar, Samir; Yadav, Kavita (IntechOpen, 2020)
Surface sciences elucidate the physical and chemical aspects of the surfaces and interfaces of materials. Of great interest in this field are nanomaterials, which have recently experienced breakthroughs in synthesis and application. As such, this book presents some recent representative achievements in the field of surface science, including synthesis techniques, surface modifications, nanoparticle-based smart coatings, wettability of different surfaces, physics/chemistry characterizations, and growth kinetics of thin films. In addition, the book illustrates some of the important applications related to silicon, CVD graphene, graphene oxide, transition metal dichalcogenides, carbon nanotubes, carbon nanoparticles, transparent conducting oxide, and metal oxides.